A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENT OF SMKN 1 BANGKINANG IN COMPREHENDING PROCEDURE TEXTS - Resti Eka Yazmi; Fadly Azhar; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was designed to describe the student’s ability in comprehending procedure text and aimed to find out the students ability in comprehending procedure text. This research was conducted in SMKN 1 Bangkinang that has been collected in February 2018. The subject of this research was XI TKJ 1 (34 students chosen by cluster random sampling. The result showed that the ability ofthe eleventh grade students of SMKN 1 Bangkinang in comprehending procedure text was in good level whosepecentage was 41.1%. Therefore, this research recomended the students to improve their grammar and choose the reading content wisely..Key Words : Student’s Ability, Procedure Text